MODELING FOR COAL WINNING MACHINE CUTTING PART IN TRANSMISSION SYSTEM AND ITS DYNAMICS ANALYSIS - MAO Jun; LIU XiaoNing; CHEN HongYue; SONG QiuShuang (Jixie qiangdu)
Based on the theory of rigid-flex coupled multi-body system dynamics,systematic research has conducted on transmission system of a coal winning machine’s cutting part. By using the software of Recur Dyn,the model was established including transmission gears,drive shaft and bearing. Considering the flexible characteristics of drive shaft,the rigid-flexible coupled model was built.Transmission system of a coal winning machine’s cutting part was simulated dynamics analysis before contact parameter setting on the parts of transmission system. The working process of shearer transmission system was described intuitively and dynamically. Results showed that 11 th gear mesh together is the biggest,11272634. 4 N.4 th. The maximum strain,measured at the axes of 4,is 0. 081. It reveals the difference of Gear meshing force curve and its frequency-domain information between Rigid-flexible coupling system and Stiff systems. Results provide a basis for optimum design of the transmission system and prediction of fatigue life.